Complex interventions. Issue 1 (31st December 2022) - Bates, Geoff
ABSTRACT: Methods of analysis in systematic reviews of interventions continue to develop as authors seek to answer questions about not only whether interventions work, but how and why they work. As our knowledge improves about how complexity in intervention design, implementation and context explains the variation in the association between interventions and outcomes, systematic reviewers increasingly seek to understand this complexity. This article explores how authors of systematic reviews can through their analysis provide the evidence that supports our understanding of how sport and exercise psychology interventions are intended to work and how complexity in the interventions themselves and in the environment they are introduced into may explain the variation in their impacts. It identifies key methods and tools to support reviewers to understand and analyse complexity in interventions, illustrated with examples from sport and exercise psychology. While complexity can be challenging to incorporate into an analysis of interventions in a systematic review, it is an important step for reviewers to take to make sense of large and complex bodies of evidence and to inform the efficient development and adaptation of interventions.